The filamentation instability of nonparaxial laser beam inside magnetized plasma - Munther B. Hassan; Ibtisam Jaafer Abd-Ali; Ahmed Obaid Soary (Results in Physics, 2019)
The filamentation instability (self-focusing) of laser beam propagating through magnetized plasma is occurring under the effect of nonlinear relativistic force. Taking into account the nonparaxial ray approximation, the laser beam of initial intensity (I ∼ 1019 W/cm2) is interacting with collisionless plasma to excite a positive lens that is leading to self-focus of the laser beam. The longitudinal static magnetic field is playing a significant role for increasing the self-focusing behavior of laser beam. The numerical results demonstrated that the self-focusing of the nonparaxial laser beam was lower than that of the paraxial laser beam. Keywords: Filamentation instability, Plasma density, Nonparaxial ray, Relativistic nonlinearity